Sympathetic Nervous System Activation and Its Modulation: Role in Atrial Fibrillation - Carnagarin, Revathy; Kiuchi, Marcio G.; Ho, Jan K.; Matthews, Vance B.; Schlaich, Markus P. (Frontiers in Neuroscience, 2019)
The autonomic nervous system (ANS) has a significant influence on the structural integrity and electrical conductivity of the atria. Aberrant activation of the sympathetic nervous system can induce heterogeneous changes with arrhythmogenic potential which can results in atrial tachycardia, atrial tachyarrhythmias and atrial fibrillation (AF). Methods to modulate autonomic activity primarily through reduction of sympathetic outflow reduce the incidence of spontaneous or induced atrial arrhythmias in animal models and humans, suggestive of the potential application of such strategies in the management of AF. In this review we focus on the relationship between the autonomic nervous system, sympathetic overdrive and the pathophysiology of AF, and the potential of sympathetic neuromodulation in the management of AF. We conclude that sympathetic activity plays an important role in the initiation and maintenance of AF, and modulating ANS function is an important therapeutic approach to improve management of AF . Potential therapeutic applications include pharmacological inhibition with central and peripheral sympatholytic agents and various device based approaches. While the role of the sympathetic nervous system has long been recognized, new developments in science and technology in this field promise exciting prospects for the future.